Proceedings of the 6th ACM SIGPLAN International Workshop on Libraries, Languages and Compilers for Array Programming 2019
DOI: 10.1145/3315454.3329954
|View full text |Cite
|
Sign up to set email alerts
|

Finite difference methods fengshui: alignment through a mathematics of arrays

Abstract: Numerous scientific-computational domains make use of array data. The core computing of the numerical methods and the algorithms involved is related to multi-dimensional array manipulation. Memory layout and the access patterns of that data are crucial to the optimal performance of the array-based computations. As we move towards exascale computing, writing portable code for efficient data parallel computations is increasingly requiring an abstract productive working environment. To that end, we present the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Burrows et al (2018) identified an array API for FDM solvers. Chetioui et al (2019) followed up with a formalization of the identified array API using MoA. We will first give an overview of PDE solvers as described by Burrows et al (2018), and an introduction to the corresponding MoA theory.…”
Section: Identifying and Formalizing The Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…Burrows et al (2018) identified an array API for FDM solvers. Chetioui et al (2019) followed up with a formalization of the identified array API using MoA. We will first give an overview of PDE solvers as described by Burrows et al (2018), and an introduction to the corresponding MoA theory.…”
Section: Identifying and Formalizing The Domainmentioning
confidence: 99%
“…of Chetioui et al (2019), and implement hardware-agnostic and hardware-dependent rewriting rules. We show how they can be applied to our Magnolia program, and measure the resulting performance improvements.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations